1998
DOI: 10.1002/biof.5520080120
|View full text |Cite
|
Sign up to set email alerts
|

Plasma antioxidants are strongly affected by iron‐induced lipid peroxidation in rats subjected to physical exercise and different dietary fats

Abstract: Plasma is an important vehicle through which antioxidant molecules are conveyed and in which they may show different behaviors, either acting as a protective factor for oxidative damage to different blood elements or using it as a vehicle through which dietary antioxidant factors would be distributed to the body. The aim of the study was to determine the plasma level of vitamin E, coenzyme Q, uric acid and vitamin A and their relation with the cellular oxidative damage mediated by physical training and the ing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1999
1999
2012
2012

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…Special attention has been focused on the type of fat more than on the total amount consumed [21]. It has been reported that virgin olive oil (rich in monounsaturated fatty acids) protects plasma and subcellular membranes against oxidative damage better than seed oils (rich in polyunsaturated fatty acids) [5,[14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Special attention has been focused on the type of fat more than on the total amount consumed [21]. It has been reported that virgin olive oil (rich in monounsaturated fatty acids) protects plasma and subcellular membranes against oxidative damage better than seed oils (rich in polyunsaturated fatty acids) [5,[14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…The hydroperoxide content of rats fed olive oil were lower than those of rats fed a diet rich in PUFA, being approximately twofold lower in the liver both after regular exercise and after regular exercise plus acute exercise. Plasma hydroperoxides showed a similar pattern [30]. In relation to antioxidant levels, coenzyme Q was strongly affected by physical exercise and to a lesser degree by dietary lipid source.…”
Section: Oxidative Stress Related To Physical Exercise and Olive Oilmentioning
confidence: 81%
“…However, involvement in sport is also a possible mechanism by which free radicals are generated, and it has been widely recognized as capable of producing peroxidative damage, mainly at the mitochondrial level, as a consequence of the net increase in oxygen consumption during sporting exercise. We have been working for several years on the effects of dietary lipid sources with different degrees of unsaturation on oxidative stress and mitochondrial function during exercise [7,8,15,29,30] using the following approach. Two groups of rats were fed diets differing in the dietary fat source: virgin olive or sunflower oils.…”
Section: Oxidative Stress Related To Physical Exercise and Olive Oilmentioning
confidence: 99%
“…We found that hydroperoxides in plasma, skeletal muscle, and liver mitochondrial membranes increased when rats were subjected to physical training, and this increase was higher when animals were fed a polyunsaturate-based diet. 32 Trained animals fed a virgin olive oil-enriched diet had lower blood triacylglycerol and cholesterol values and a modified fatty acid profile in both plasma and tissue according to the fat ingested. 33,34 Coenzyme Q, vitamin E, vitamin A, and uric acid all underwent dramatic changes, with sharp decreases in blood and concomitant increases at the mitochondrial level, suggesting a mobilization of these molecules among body compartments depending on local needs during and after training.…”
Section: Physical Training and Protection Offered By Dietmentioning
confidence: 98%